2015
DOI: 10.1117/1.jbo.20.4.046003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium dioxide nanoparticles coupled with diode laser on optical properties ofin vitronormal and cancerous human lung tissues studied with optical coherence tomography and diffuse reflectance spectra

Abstract: The objective is to investigate the effects of two different sized (60 and 100 nm) titanium dioxide (TiO2) nanoparticles (NPs) penetration and accumulation in in vitro human normal lung (NL) tissue, lung squamous cell carcinoma (LSCC) tissue, and 650-nm diode laser-pretreated tissue on their optical properties studied with optical coherence tomography monitoring and diffuse reflectance (DR) spectra measurement. As with TiO2 NPs penetrating into the tissues, the intensities of DR of the samples increase, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…38 It has been reported that the bottom surface of the flow cell can serve as a reference surface whose relative position and reflectivity can be used for the estimation of the refractive index and thickness of the biofilms. 21 In the present experiment, the OD is altered by the varying concentration of bacterial cells or microcolonies leading to a subdued intensity from the bottom surface, according to the relation 16,38 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 2 ; 6 3…”
Section: Optical Density Measurement Using Ocm Techniquementioning
confidence: 88%
See 1 more Smart Citation
“…38 It has been reported that the bottom surface of the flow cell can serve as a reference surface whose relative position and reflectivity can be used for the estimation of the refractive index and thickness of the biofilms. 21 In the present experiment, the OD is altered by the varying concentration of bacterial cells or microcolonies leading to a subdued intensity from the bottom surface, according to the relation 16,38 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 0 2 ; 6 3…”
Section: Optical Density Measurement Using Ocm Techniquementioning
confidence: 88%
“…On the contrary, in vivo and label free imaging of biofilms at large working distances and improved depth can be achieved by optical coherence tomography (OCT). [16][17][18][19] OCT allows depth resolved high-resolution cross-sectional and volumetric imaging of biological specimens up to a few millimeters of depth. 20 The mean biofilm thickness obtained from the cross-sectional images provides a measure of the spatial size of the biofilm and is the most common variable used in biofilm literature to quantify the growth.…”
Section: Introductionmentioning
confidence: 99%
“…All spectra measurements were recorded with the integration time set to 100 ms. The measurements were recorded and stored into a computer for the further postprocessing [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Zhou et al [26] studied the effects of titanium dioxide nanoparticles coupled with diode laser on optical properties of in vitro normal and cancerous human lung tissues studied with OCT and diffuse reflectance spectra. In this paper, a scheme was designed to explore the differences of optical spectra and OCT backscattered light intensities between the LI4 acupoint and its adjacent acupoints after a 658 nm laser irradiation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a research group reported [13] an ex vivo study on the penetration dynamics of TiO 2 NPs into human tissues with 830 nm OCT and diffusion reflectance (DR) spectra. The effects of TiO 2 NP penetration on the optical properties of both normal and cancerous lung tissue have also been studied [14].…”
Section: Introductionmentioning
confidence: 99%